Post-operative Pain after Lichtenstein Inguinal Hernia Repair - Muhammad Ilyas Riaz, Iftikhar Ahmed, Asma Bibi, Fatima Usman, Adeel Ur Rehman Kandaan, Amna Bibi, Shahid Mahmood, Naeem Zia (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Although advanced techniques have been adopted in inguinal hernia repair parallel to those in developing medical technologies, currently no consensus has been reached on the best method among all existing methods. Post-operative pain is the main reason for longer hospital stay, repeated visits in out-patient department (opd) and delay in return to daily routine work. Objective: To compare the mean post-operative pain of Lichtenstein procedure with and without mesh fixation for inguinal hernia repair Methodology: This randomized control trial was conducted for 6 months in Benazir Bhutto Hospital, Rawalpindi. Patients were divided into two groups, Group-A included those managed without mesh fixation and Group-B who had mesh fixation. All the patients were assessed for postoperative pain at 24 hours by visual analogue scale (VAS). Results: In our study, comparison of mean post-operative pain score in both groups shows 3.23+0.77 in Group-A and 3.98+0.76 in Group-B, p value was 0.0001. Conclusion: We concluded that post-operative pain is less in patients managed by Lichtenstein repair without mesh fixation as compare to patients managed with mesh fixation Keywords: Inguinal hernia, Lichtenstein procedure, mesh fixation, post-operative pain